PENGGUNAAN LEMBAR KERJA SISWA MODEL GUIDED NOTE TAKING DALAM MENINGKATKAN HASIL BELAJAR SISWA SMK MUHAMMADIYAH BULUKUMBA - Nasrun, Muh (Jurnal Riset Guru Indonesia, 2023)
This study uses the ex post facto method, namely by collecting data such as data on learning achievement scores based on the average before getting treatment and after getting treatment or treatment. The population in this study were 18 students of Class XII of the Computer and Network Engineering Department of Muhammadiyah Bulukumba Vocational School. To determine the size of the sample in this study using a non-probability technique, namely the saturated sample technique using the entire population as a sample, namely as many as 18 students. Data collection techniques used are observation techniques, interviews, documentation and evaluation tests. The data analysis technique used is the arithmetic mean method. The results of this study indicate that the average student learning outcomes reached 6.72 before using the GNT Model Student Worksheet, after being treated or using the GNT model LKS, the value of learning outcomes increased with an average value of 8.98.